Intravenous immunoglobulin and prednisolone to women with unexplained recurrent pregnancy loss after assisted reproductive technology treatment: a protocol for a randomised, double-blind, placebo-controlled trial - Ulrik Schiøler Kesmodel; Kaspar Nielsen; Rudi Steffensen; Caroline Nørgaard-Pedersen; Line Eriksen; Malene Møller Jørgensen; Ole Bjarne Christiansen (BMJ Open, 2022)
Introduction Recurrent pregnancy loss (RPL), defined as two or more consecutive pregnancy losses in the first trimester, affects around 5% of fertile women. The underlying causes remain unknown in up to 60% of patients; however, most studies point at an immunological pathology in unexplained RPL, and therefore, an effective treatment may be immunomodulatory. This study aims to evaluate the effect of intravenous immunoglobulin (IVIg) and prednisolone on reproductive outcome and the immune system in women with unexplained RPL undergoing assisted reproductive technology treatment.Methods and analysis This randomised, placebo-controlled trial with double-blinded randomisation to two parallel arms evaluate if immunomodulatory (active) treatment is superior to placebo in increasing the chance of ongoing pregnancy assessed at nuchal translucency scan in gestational weeks (GW) 11–13 after embryo transfer (ET) in 74 RPL patients with ≥2 pregnancy losses as its primary objective. The active treatment consists of IVIg (one infusion preferably 1–5 days before ET and in GW 5, 6 and 7) and prednisolone (5 mg/day from first day of menstrual bleeding until ET and 10 mg/day from ET to GW 8+0) while the comparator consists of intravenous human albumin (5%) and placebo tablets. Allocation is concealed for participants, caregivers, and investigators until trial termination and is performed in a 1:1 ratio. The secondary objective is to evaluate treatment safety, and the tertiary objective is exploration of the association between treatment, reproductive outcome after ET, and the lymphocyte subset distribution in peripheral blood collected before and after intravenous infusion(s). Excess biological material is stored in a biobank for future research.Ethics and dissemination The North Denmark Region Committee on Health Research Ethics (N-20200066) approved this trial. The results will be published in peer-reviewed scientific journals and presented to relevant patient associations, at relevant academic conferences and to key stakeholders.Trial registration number NCT04701034.